Milk-Clotting Properties and Primary Proteolysis of a Lyophilised Extract from Artichoke Flowers (Cynara scolymus L.) - Crosetti, Valentina; Sola, Agustín; Grigioni, Gabriela Maria; Torres, María José (Facultad de Tecnología de Alimentos y Biotecnología, Universidad de Zagreb, 2023)
Research background: A few studies have investigated Cynara scolymus enzymes as a substitute for calf rennet in cheese making. They used aqueous extracts prepared by maceration of plant material and stored by freezing. However, it was indicated that lyophilisation is a better alternative to preserve the coagulant properties of plant extracts over a longer period of time, as it is a more controllable, stable and hygienic alternative with a better shelf life that is easier to transport, store and standardise. Experimental approach. We obtained a lyophilised extract of mature artichoke flowers, named CS, which was characterised for its milk-clotting properties at different pH and temperatures. In addition, the potential yield, whey composition and the primary hydrolysis profile of caseins by urea-polyacrylamide gel electrophoresis (PAGE) of mini curds prepared with different doses of coagulant were determined. Results and conclusions: The lyophilised extract was able to hydrolyse casein and showed stable proteolytic activity at pH=6.4 and 37 °C for 50 min, which decreased when the process temperature was increased to 41 and 45 °C and was lost at 70 °C. On the other hand, milk-clotting activity increased significantly (p<0.001) when the temperature increased from 37 to 45 °C and the pH of the milk decreased from 6.8 to 5.8. Potential yield between 10 and 17 % was obtained for the mini curds prepared with the lyophilised artichoke extract, and the casein degradation pattern obtained by urea-PAGE was similar to that of the commercial coagulant. Novelty and scientific contribution: On a laboratory scale, our work has shown that the lyophilised artichoke extract has sufficient proteolytic and coagulant activity to be used as a milk coagulant, i.e. plant rennet, in cheese making as an alternative to animal rennet. As this extract is lyophilised, it has the advantage of being a better alternative in terms of preservation and shelf-life. It offers an innovative way to diversify cheese products and appeal to consumers with different dietary preferences and needs.